2022
DOI: 10.1038/s41390-022-02136-2
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin for iron-deficiency anemia in children with inflammatory bowel disease: a clinical trial

Abstract: Background Iron-deficiency anemia (IDA) is common in children with inflammatory bowel disease (IBD); however, oral iron supplements are commonly associated with poor compliance due to gastrointestinal side effects. We compared the effect of lactoferrin versus oral ferrous sulfate for the treatment of IDA in children with IBD. Methods Ninety-two IBD children with IDA were included but only 80 children completed the study and they were randomized into two gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 23 publications
(22 reference statements)
1
9
0
1
Order By: Relevance
“…This represented 68% of all participants involved in the trials [ 19 , 21 – 23 , 25 , 26 , 28 , 29 , 33 – 35 ]. Seven trials (37%) involved children aged over 2 [ 24 , 27 , 30 – 32 , 36 , 37 ], and one trial targeted cancer patients undergoing chemotherapy [ 20 ]. Additionally, four trials included 334 individuals with chronic health conditions (cancer, cerebral palsy, inflammatory bowel disease, obesity), all of whom had anemia (Hb < 11.5 g/dL) [ 20 , 27 , 32 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This represented 68% of all participants involved in the trials [ 19 , 21 – 23 , 25 , 26 , 28 , 29 , 33 – 35 ]. Seven trials (37%) involved children aged over 2 [ 24 , 27 , 30 – 32 , 36 , 37 ], and one trial targeted cancer patients undergoing chemotherapy [ 20 ]. Additionally, four trials included 334 individuals with chronic health conditions (cancer, cerebral palsy, inflammatory bowel disease, obesity), all of whom had anemia (Hb < 11.5 g/dL) [ 20 , 27 , 32 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…The difference in the mean Hb values among groups were statistically insignificant. LF was equally effective in improving Hb concentration levels as the other two trialled oral iron preparations El Amrousy et al (2022) [ 27 ] Egypt 80 children with inflammatory bowel disease, suffering with IDA, aged between 5–18 years 40 participants 100 mg per day 40 participants Ferrous sulfate 6mg/kg/day Hb concentration levels were significantly increased in both groups. However, the LF group had a significantly higher mean Hb value than the ferrous sulfate group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that oral iron is poorly tolerated and may increase mucosal inflammation, it is only applicable to IBD patients in the quiescent phase ( 58 ). However, some new oral iron agents, such as lactoferrin and ferric maltol, have also shown good safety and tolerance, and are promising forms of iron supplements that are expected to replace standard oral iron agents ( 47 , 59 ). Concerning intravenous iron, many clinicians worry about its allergic reactions ( 60 ), but more and more studies have confirmed the safety of intravenous iron supplementation (mainly ferric carboxymaltose) ( 61 , 62 ), and the reaction rate of intravenous iron is higher than that of oral iron ( 63 ).…”
Section: Mineralsmentioning
confidence: 99%
“…Inflammatory bowel disease (IBD) is a chronic condition that can last a lifetime and reoccur, causing inflammation, diarrhea, rectal bleeding, and abdominal pain due to severe anatomical damage, immune overactivation, oxidative stress, and microbiome disruption [ 1 , 2 ]. Ulcerative colitis (UC) primarily affects the rectum and colon, leading to inflammation, pain, and diarrhea, including mucous and bloody stool, resulting in anemia and iron deficiency [ 1 , 3 ] as well as a greater risk factor for colon cancer, the second leading cause of cancer death globally [ 4 , 5 ]. Crohn’s disease (CD) involves chronic inflammation of the distal gut, leading to lesions along the entire intestine, immune intolerance of commensals, fever, tiredness, and complications such as stenosis, fistulas, and strictures [ 6 ].…”
Section: Introductionmentioning
confidence: 99%